THE THEATRE OF VIRGÍNIA VICTORINO AND THE FIRST PORTUGUESE REPUBLIC - SILVA, FABIO MARIO DA (Revista Alere, 2015)
Virgínia Victorino’s plays addressed the needs of bourgeois audiences at the beginning of the 20 th century, leaving behind themes of love and relationships, and entering the notional and ideological field of new Portuguese Republican politics. Her plays attracted the acclaim of their audiences, the criticism of journalists (from Brazil and Portugal) and draw in representatives of the Portuguese government. It is within this context that the author attempts to find ways in which to better attend to new Portuguese social norms, while at the same time continuing to include in her plays, more so than in her poetry, elements of her political stance, which is frequently controversial. In this way, the work of Virgínia Victorino reflects the intrinsic problems of the new Portuguese Republican political system.